Think Pair Share with Drill Method: A teaching Learning Strategy to Enhance Students’ Arabic vocabulary mastery - Hasibuan, Renni; Jundi, Muhammad (Educational Journal of Learning Technology, 2024)
Exploring the implementation of the Think Pair Share model with the drill method in Arabic vocabulary learning is the main objective of this research. Using a qualitative approach through interviews and observations, data analysis was conducted iteratively and in-depth. The research findings indicate that there are four steps in implementing the Think Pair Share model with the drill method in Arabic vocabulary learning. First, the teacher introduces new vocabulary and explains its meaning and usage in sentences to the students. Then, students are given time to process and understand the vocabulary they have just learned through the thinking stage. Next, students are paired with classmates to share and memorize the vocabulary they have learned in turn. Finally, the results of the discussion are shared with the whole class, where the teacher selects several pairs randomly to come forward and convey their understanding of the vocabulary and its meaning to the entire class.